PICTURE SERIES TO INCREASE WRITING SKILL OF EFL JUNIOR HIGH SCHOOL STUDENTS - Rahma, Reza Ainur; Anwar, khoirul (Journal Universitas Muhammadiyah Gresik Engineering, Social Science, and Health International Conference (UMGESHIC), 2021)
The purpose of this study was to find out whether picture series media was effective on writing knowledge in EFL students of eighth grade at SMPN 31 Gresik in the 2020/2021 school year. The participants in this study were students in eighth grade at SMPN 31 Gresik. The number of samples in this study was 64 students. The classes are divided into two classes; experimental class and controlled class. The method used is a quantitative method that adopts a quasi-experimental design. The instrument used was a recount text writing test consisting of a pre-test and a post-test. After collecting student scores from the two tests, the author uses SPSS v.22 to analyze normality and homogeneity to determine whether the data are normally distributed and homogeneous or not. After analyzing the normality and homogeneity, the writer also tested the hypothesis by using a paired sample test to determine whether there was the effectiveness of using picture series in learning to write recount text. The study's findings found that the average post-test score in the experimental class was higher than the post-test mean in the control class (82.58 > 53.20). Furthermore, the paired sample test analysis proved that the post-test p-score was 0.00 with a significance level of 5% (0.05). In other words, it can be concluded that the p-value (0.00) there is a significant difference between students' writing recount text using picture series and without picture series. That is, picture series is effective and applicable as a medium in writing recount text.